1998
DOI: 10.1108/01443339810788380
|View full text |Cite
|
Sign up to set email alerts
|

Drug testing in the workplace: the allure of management technologies

Abstract: Discusses US use of drug testing in the workplace, screening employees for smoking, AIDS, genetic traits and reproductive hazards. Attributes this to the costs employers face in insurance, litigation and compensation. Points out that the purpose of drug testing is to circumvent management responsibility for: accidents in the workplace, stress, bad management practices, and disregarding health and safety initiatives. Acknowledges that the tests are harmful and indefensible. Reports that 81 per cent of members o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…He suggested that social ceremonies involving scapegoats, magical or medical, serve to unite individuals in groups by identifying a common menace linked to a deviant practice. By way of illustration in an organisational context, both Gilliom (1994) and Draper (1998) have argued that drug users have functioned as a convenient scapegoat upon which management may shift responsibility for health and safety concerns in the workplace. Widening the focus further, it is important to note how certain other groups have also been identified as menacing for the social order.…”
Section: The Symbolic Image Of a Supermodelmentioning
confidence: 98%
See 2 more Smart Citations
“…He suggested that social ceremonies involving scapegoats, magical or medical, serve to unite individuals in groups by identifying a common menace linked to a deviant practice. By way of illustration in an organisational context, both Gilliom (1994) and Draper (1998) have argued that drug users have functioned as a convenient scapegoat upon which management may shift responsibility for health and safety concerns in the workplace. Widening the focus further, it is important to note how certain other groups have also been identified as menacing for the social order.…”
Section: The Symbolic Image Of a Supermodelmentioning
confidence: 98%
“…Some argue that the economic-cultural context which encourages high achievement and success seems to instigate the use of performance-enhancing strategies, including the use of stimulants, smart drugs vitamins or illegal drugs, the case of sports drug use being one of the prominent examples, but applicable to other demanding professions (Reinerman and . Similarly, evidence poor is that organisational responses to the actual or perceived threat of drugs have been efficacious in reducing employee drug use (Jardine-Tweedle and Wright 1998) or in helping employees' health (Draper 1998). In the light of such critiques, some have questioned whether anti-drug policies and workforce drug testing should actually be understood as a response, rational or not, to drug use at all.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, other studies (French et al 2004) show how drug testing creates several unintended effects for employers, as it effectively deters prospective applicants and generates additional costs related to staff turnover, increased staff recruitment, and administration of the drug tests. Underlying these mixed results are the differences among the types of settings and people being tested (Borg 2000;Borg & Arnold 1997;Boyes-Watson 1997;Draper 1998;Haapanen et al 1998;Kleiman et al 2002;Knudsen et al 2003;Turner & Petersilia 1992).…”
Section: Key Issues Surrounding Drug Testingmentioning
confidence: 99%
“…Attitudes towards the use of drugs from marijuana to spousal prescriptions, indeed the very definition of a drug-for example, the commonplace separation of alcohol from other drugs-vary widely (American Civil Liberties Union 1999). Workplace drug testing is still relatively rare in Europe but in the United States managerial control is noted as an underlying value of workplace drug testing (Cavannaugh and Pushkala 1994;Draper 1998;Gilliom 1994). When workplace drug testing is on the collective bargaining agenda, union concerns are raised regarding regulation of off duty conduct, privacy of medical information, and stigmatization of workers who test positive.…”
Section: Union Members Divided On Issue Of Workplace Drug Testingmentioning
confidence: 99%